Catalogue of Solanaceae of La Libertad region, Peru - Rodríguez Rodríguez, Eric F.; Herbarium Truxillense (HUT), Universidad Nacional de Trujillo, Jr. San Martín 392, Trujillo (2020)
We provide a catalogue of the Solanaceae family of La Libertad region, Peru. The study was based on new collections made by the authors in recent years, on the reviews of a significant number of herbarium specimens and specialized bibliography. A total of 22 genera, 173 species and 8 varieties were registered; including 20 cultivated species and 78 endemic taxa. Browallia, Iochroma, Jaltomata and Solanum present the highest number of species of the total family (119 sps.; 68,79%) and the highest number of endemisms (64 sps.; 82,05%). Endemic taxa according to their degree of threat are categorized: Critically Endangered (CR) (30), Endangered (EN) (8), Vulnerable (VU) (16), Near Threatened (NT) (9), Least Concern (LC) (3), Data Deficient (DD) (7), Not Evaluated (NE) (5). Browallia, Iochroma and Jaltomata are the genera whose species present the highest degree of threat (CR). 13 endemic species are found in protection areas [Calipuy National Reserve and Lomas Cerro Campana Private Conservation Area (PCA)]. The material examined for each species includes the geographical distribution according to the provinces and altitudes, the common name if it existed, the type specimen only of the material described for the La Libertad region, marked by the name and number of the main collector, followed by the acronym for the herbarium where it is deposited; as well as the current state of conservation of the taxon only in the case of endemic taxa. The threats and destruction of the species’ habitats are due to anthropic action. The information presented will serve to continue research in taxonomic, ecological, environmental, molecular aspects, obtaining bioactive compounds and innovation.